High crystalline magnetic covalent organic framework with three-dimensional grapevine structure for ultrasensitive extraction of nitro-polycyclic aromatic hydrocarbons in food and environmental samples. (1st November 2021) - Wang, Xiao-Xing; Liu, Lu; Wang, Xiao-Li; Xu, Gui-Ju; Zhao, Ru-Song; Wang, Ming-Lin; Lin, Jin-Ming; Wang, Xia
Highlights: A novel high crystalline Fe3 O4 @TAPT-DMTA-COF with grapevine shape was fabricated. Structural particularity made this own supermagnetism and lager surface area. The method was faster and more sensitive for N -PAHs than existing methods. This MSPE technique was applied to quantify N -PAHs in food and water samples. Possible adsorption interaction mechanism was elucidated. Abstract: Developing and establishing an efficient pre-treatment approach for the precise extraction of nitrated-polycyclic aromatic hydrocarbons ( N -PAHs) from real-life samples is critical for ensuring their safety. In this study, a novel crystalline magnetic covalent organic framework with a grapevine structure not a single core–shell, Fe3 O4 @TAPT-DMTA-COF, was fabricated via chemical bonding. Unchanging the reticulated structure and high crystallinity of TAPT-DMTA-COF, the combination made this material possess not only simple operation via magnetic decantation but also remarkable chemical stability. Fe3 O4 @TAPT-DMTA-COF had a large surface area (1578.45 m 2 /g), and rich electronegative triazine-groups, which makes it become a superior magnetic enrichment material for trace N -PAHs. For N -PAHs analysis, low limits of detection (LODs) (1.43–17.24 ng/L), excellent relative standard deviations (RSDs ≤ 11.52%), and wide linearity (10–5000 ng/L) were obtained. Real-life applications based on this composite have been successfully explored by capturing the N -PAHs emitted from food and environmental samples.